2000
DOI: 10.1136/heart.84.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Exercise echocardiography predicts development of left ventricular dysfunction in medically and surgically treated patients with asymptomatic severe aortic regurgitation

Abstract: Objective-To assess resting and exercise echocardiography for prediction of left ventricular dysfunction in patients with significant asymptomatic aortic regurgitation. Design-Cohort study of patients with aortic regurgitation. Setting-Tertiary referral centre specialising in valvar surgery. Patients-61 patients (38 men, 23 women; mean (SD) age 53 (14) years) with asymptomatic or minimally symptomatic aortic regurgitation and no known coronary artery disease; 35 were treated medically and 26 had aortic valve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 34 publications
(17 reference statements)
1
59
1
4
Order By: Relevance
“…This appears to be valid in patients undergoing AVR and in those on medical treatment. 9 The added usefulness of CR in determining the timing of AVR, and the relationship of CR to other baseline characteristics have not been fully defined. Hence, we performed resting and exercise echocardiography to assess CR in asymptomatic or mildly symptomatic patients with severe AR and to determine potential clinical applications of CR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This appears to be valid in patients undergoing AVR and in those on medical treatment. 9 The added usefulness of CR in determining the timing of AVR, and the relationship of CR to other baseline characteristics have not been fully defined. Hence, we performed resting and exercise echocardiography to assess CR in asymptomatic or mildly symptomatic patients with severe AR and to determine potential clinical applications of CR.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,17,18 Also, CR may be useful in monitoring the early development of myocardial dysfunction in asymptomatic patients with AR. 9 To evaluate the presence of CR in AR, exercise stress echocardiography should be performed. A previous study found no correlation between LVEF response to exercise and resting LV dimensions or LVEF in a group of patients with AR compared to normal controls.…”
Section: Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed magnitude of change in ejection fraction or stroke volume from rest to exercise is related not only to myocardial contractile function but also to severity of volume-overload and exercise-induced changes in pre-load and peripheral resistance (1). The validity of stress echocardiography in predicting outcome of patients with asymptomatic AR is limited by the small number of available studies (39,40) compared with the more extensive and consistent experience with exercise radionuclide angiography (41)(42)(43)(44). With the sparse data supporting the incremental prognostic value of stress echocardiography, this specific application is not recommended for routine clinical use (1).…”
Section: Aortic Regurgitation (Ar)mentioning
confidence: 99%